Online courses on open source software usage by an academic library - Papazoglou , C.; Dagdilelis, V.; Margaritis, K.; Fragkou, A. (Proceedings of the International Conference on Networked Learning, 2008)
Until recently, academic libraries were viewed as a supportive factor in the learning process and their role was restricted to material provision. Over the last few years, though, the role of libraries in the learning process is being re-evaluated. One area in which libraries are expected to play an active teaching role is information literacy skills. The main purpose of information literacy programs is to enable students to evaluate information and its sources critically and incorporate selected information into his or her knowledge base and value system. During the last few years, the world has also witnessed major changes in teaching and learning paradigms. In particular, asynchronous e-learning has emerged as the learning method of choice in many education scenarios. The widespread adoption of this teaching technique is fueled by the global connectivity provided by the Internet which allows students to access material and tutors virtually anytime and from any location. Combining the trends and requirements described above the Library and Information Center of the University of Macedonia (UOM) created a virtual learning environment called Telemathea (http://telemathea.uom.gr) using Moodle, a freely available open source course management system. In the context of the 3rd Community Support Framework and the PLOEGIS project in particular, the UOM Library embarked on the development of online courses with the help of University Professors. The topic of the administered courses was selected to be computer usage with free and open source software. This choice was motivated on one hand by the importance of basic computer skills as a component of information literacy and on the other hand by the intention of both the Library and the University to promote free and open source software. Separate courses were created for both Linux and Microsoft Windows users with different content depending on the operating system. All teaching and learning was performed asynchronously via the Telemathea virtual learning environment and did not require the presence of students in a classroom at any point. The selected audience was not restricted to Library users but instead encompassed people of various ages and occupations located in several Greek cities. The course content was based on material granted by the ICDL (International Computer Driving License) Foundation. The audience was selected after a public call. Course design and preparation was handled by Library personnel in cooperation with University of Macedonia Professors. This paper describes the e-learning seminar conducted by the UOM Library during the first semester of 2007 which included the courses on web browsing and e-mail. During a period of 2 months, 47 people (30 Windows users and 17 Linux users) “attended” the online courses. Among the issues covered in this paper is the design and construction of online courses, the supervision of courses while they were offered to students, the statistics of student activity and the conclusions of the evaluation of both the courses and the learning environment from the viewpoint of students. Several interesting conclusions that were drawn during the evaluation process are presented, including the creation of a virtual classroom, the social interaction between learners, and the communication of learners with teachers.